Maqāṣid Mediation Balances Gender Justice in Islamic Inheritance: Mediasi Maqāṣid Menyeimbangkan Keadilan Gender dalam Waris Islam - Husni, Husni; Yul, Widiya; Rahmatullah, Prayudi (Academia Open, 2026)
General Background Islamic inheritance is a central component of Islamic family law explicitly regulated by the Qur’an and Hadith, yet it remains debated because of gender-based disparities in relation to justice and public welfare. Specific Background This study examines contemporary debates on gender justice in Islamic inheritance law through a structured review of reputable journal articles published between 2015 and 2025, guided by hermeneutical reading and the maqāṣid al-sharīʿah perspective. Knowledge Gap Previous studies have often remained within two opposing poles, namely textualist-apologetic defense of the 2:1 inheritance ratio and revisionist-contextual demands for equal shares, without offering an integrative Islamic epistemological synthesis. Aims This study analyzes the normative basis of inheritance distribution, evaluates classical and modern debates on unequal inheritance rights, and offers a reinterpretive framework grounded in internal Islamic hermeneutics, maqāṣid al-sharīʿah, and maṣlaḥah. Results The study maps three major positions: textualist-apologetic, revisionist-contextual, and Islamic feminist critiques. It also reveals a movement toward proportional justice, where inheritance rights are considered in relation to real economic responsibility and contribution, especially when a person functions as the main provider. Novelty The study formulates maqāṣid al-sharīʿah as a manhaj wasaṭī, or mediating framework, that integrates textual authority, socio-historical context, and substantive justice. Implications This framework supports a contextual yet textually grounded understanding of Islamic inheritance law for inclusive and gender-responsive legal reasoning. Highlights• Proportional fairness links shares with actual economic responsibility.• Three scholarly positions are mapped across textualist, contextual, and feminist debates.• Wasathiyyah reasoning connects scriptural authority with changing social realities. KeywordsGender Justice; Islamic Inheritance; Maqāṣid Al Sharīʿah; Islamic Hermeneutics; Family Law